Pemberian Pmt Modifikasi Berbasis Kearifan Lokal Pada Balita Stunting dan Gizi Kurang - Irwan Irwan (Univeristas Negeri Gorontalo, 2019)
The formula given to children who are malnourished / deficient in accordance with the standards set by the World Health Organization (WHO) is made from oil, sugar, milk, water and flour. In addition, PMT can be made by yourself with a composition containing anergy and protein intake and made from ingredients that are easily available to the public at an affordable cost. The method of community service activities is in the form of providing additional food to 11 toddlers who have experienced nutritional problems, both malnutrition and stunting in the village of Bukit Tingki. The Focuk Group Discussion (FGD) method in the form of training activities for healthy nutrition cadres was carried out for 2 days. The results of the activity showed that the provision of additional food (PMT) modified in the form of pumpkin and corn can improve the nutritional status of children under five, as many as 11 children under five had nutritional problems, 8 of them were in the under nutrition category and 3 under five were stunted. After giving additional food, body weight increased significantly so that it became a healthy nutrition category, while 4 children under five who were previously included in the stunting category after being given Modified PMT experienced significant growth and increase in body weight. The conclusion is that giving PMT modification based on local wisdom can be an alternative program to eradicate stunting and malnutrition in villages